Pedaling patterns of professional cyclists during a grand tour - Jamar, A.; De Vries, S.; Hesselink, M. (Journal of Science and Cycling, 2015)
Introduction: Fatigue has been reported to alter Muscle activation patterns and pedaling technique in cyclists is affected by fatigue. One of the key biomechanical variables to assess pedaling technique is Index of Effectiveness (IE), defined as the ratio between effective force and total force on the crank. Although cycling is a bilateral movement, the relative contribution of the lower limbs to cycling power output is seldom symmetrical. Most studies on pedaling technique and bilateral asymmetry have been performed in laboratory settings and it is not known if, and to what extent, racing-induced fatigue affects these parameters during competition. Thus we analyzed if fatigue affected IE and Asymmetry Indices in professional cyclists during a 3-week stage race.